Associations of viral ribonucleic acid (RNA) shedding patterns with clinical illness and immune responses in Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection - Lee, P.H. (John Wiley and Sons Inc, 2021)
10.1002/cti2.1160